CURRENT TRENDS IN THE DEVELOPMENT OF BUSINESS PRODUCTS AND SERVICES IN THE CONTEXT OF DIGITAL ECONOMY FORMATION (Journal of Science-Innovative Research in Uzbekistan, 2024)
The present article shows that in the conditions of formation of digital economy on an international scale, the creation and continuous improvement of information products and services for all sectors and spheres of the economy, including bines, is of greater importance. The article shows that the development of the information component of economic objects is the basis of their competitiveness in the global economic market